Import Substitution in Russia: Historical Experience and Current Prospects - V. E. Naruzhnyy; V. A. Titov; Yu. A. Obolenskaya (Управленческое консультирование)
The article provides a brief overview of the history of import substitution in Russia. The reasons for the strategic failure of Soviet industrialization are described. The results of comparative analysis of two import-substituting leaps in post-Soviet Russia are presented. An overview of options for the use of foreign resources for the benefit of the domestic military-industrial complex (MIC) is given. Recommendations on the implementation of import substitution in the Russian MIC are formulated.